The Efficacy of Action: A Gender-Based Analysis of Self-Efficacy, Optimism, and Goal Commitment in Georgian Higher Education - Kharadze, Natalia; Gulua, Ekaterine (European Journal of Social Science Education and Research, 2025)
This study investigates the role of key personal development constructs—self-efficacy and optimism—as predictors of academic and career goal commitment among master's students in Georgia. Focusing on the critical transition from higher education to the labor market, the research places a central emphasis on identifying and interpreting gender-based differences in these psychological assets. A quantitative, cross-sectional survey was administered to 452 master's students from three major universities in Tbilisi. The survey employed the General Self-Efficacy Scale, the Life Orientation Test-Revised, and a researcher-developed Goal Commitment scale. Independent samples t-tests revealed a significant gender gap in self-efficacy, with male students reporting higher levels than their female counterparts, although no differences were found in optimism or goal commitment. Multiple regression analysis confirmed that both self-efficacy (β = .451) and optimism (β = .219) are strong, independent predictors of goal commitment, explaining 32.4% of its variance. These findings highlight a "belief versus will" paradox among female students and underscore the need for Georgian universities to integrate targeted, efficacy-building interventions into their curricula to better prepare all graduates for future success.
Keywords: Self-Efficacy, Goal Commitment, Gender Studies, Personal Development, Higher Education, Georgia, Optimism, Student SuccessSelf-Efficacy, Goal Commitment, Gender Studies, Personal Development, Higher Education, Georgia, Optimism, Student Success